O acolhimento institucional a partir da produção e dos discursos de psicólogos - Pereira, Leilane Cristina Oliveira (2020)
The present thesis aims to analyze hosting institutions based on scientific production and the discourse of psychology professionals who work in hosting institutions. Institutional care is a type of protective measure that can be taken in situations of abuse against children and adolescents. Psychology is practiced within child and adolescent care institutions equipped with a technical team that must produce quarterly reports on cases in order to contribute to the judicial analysis of the cases, in addition to daily cooperation with the shelters. It is assumed that: the scientific production of hosting psychology is mainly made and directed to academics, it is driven by new legislation; the performance of psychology in the hosting institutions is modeled by the historical construction of the profession, the models of childcare, and the discourses that are formulated and support these models of psychology and care; that psychology works by supporting the value of foster care institutions and blaming poor families of institutionally sheltered children and adolescents. Based on the assumptions presented, the thesis is defended that psychology, in its scientific production and performance in hosting institutions, is fixed to the maternal discourse, acting to guarantee rights and updating discourses of subjection of poor children. To this end, it was chosen as theoretical categories, built on the basis of Foucault's theory, discourse, and truth. Study 1 was a bibliographic search of the scientometrics type in order to fulfill the first objective. The term “shelter” was used as a search descriptor in the databases, for publications between 2005 and 2010, and the term “institutional shelter”, for publications between 2010 and 2017, in the SciELO and CAPES/MEC Journal Portal databases. Descriptive statistics were performed as data analysis. Study 2, with a view to fulfilling the other specific objectives, was carried out through the critical analysis of the discourse of interviews with 6 psychology professionals who work in hosting institutions. According to the characteristics established in the method for study 1, 54 publications were identified, 18 articles with the term "shelter" and 36 articles with the term "Institutional shelter". It was observed that, in the majority, the articles were published by women with training in psychology, linked to federal education institutions in the South and Southeast regions of Brazil and had public funding. Most of the publications involved interviews with sheltered children and adolescents and were driven by changes in legislation. The results of study 2 show that: the performance of psychology in hosting institutions is impacted by the process of feminization of work; psychology works to guarantee rights; the performance of psychology in the hosting institutions collaborates in updating the forms of subjection of poor children; and psychologists who work in hosting institutions consider that the training they received prepared them for clinical practice. From the results, it is concluded that the thesis was corroborated by psychology, in its scientific production and performance in the hosting institutions; it is fixed to the maternal discourse, acting to guarantee rights and updating discourses of subjection of poor children. In the hosting institutions, psychology is fixed to the maternal discourse in addition to suffering impacts from the feminization process of the profession.